Evaluating the effect of the Micro Finance Scheme Programme for rural entrepreneurs in Oshikoto Region, Namibia - Amadhila, Foibe Kandalindishiwo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPA)--Stellenbosch University, 2019.